Education of the sexuality and adolescents. Cognitive investigation and anthropology of reference - Romano, Lucio (Medicina e Morale, 2000)
The importance and the actuality run in the circle of the sexuality are deduced, in the article, from an investigation cognitive turn in a group of adolescents (648 students of the last year of the secondary superior school, with a middle age of 17.2 years). In the compilation of an anonymous questionnaire, the interviewed adolescents have revealed a meaningful application of share to programs of sexuality's education and of formation to the moral feeling. The demonstration of an educational need by part of the adolescents has shown from the confusion between information and education, from the uneasiness in the involve the parents or the teachers, for example, in the problematic inherent the sexuality to front of a suppository claimed acquaintance of education of the sexuality. In fact prevails a culture informed to a naturalistic anthropology and to an ideology, that has reduced the adolescence to mere consumer of an understood sexuality like well of consumption where it doesn't lodge any ethic that bases itself on the responsible opening toward the other: sexuality that is translated in sex, in only genitality where the norm has constituted of what it is biological moral, that is to say the statistic datum becomes law and determines the value. From the analysis of the questionnaire it reveals the necessity, therefore, of an education of the sexuality that continues with the circle of an integral development of the person, educational process to understand like improvement and intervention in favor of the person in his physical - spiritual global education to the sexual difference, affective and moral education, education to the value of the life. The points of reference for a correct formation of the sexuality and of the moral feeling have represented from the unitotality of the person, opening to the love, complementary, inseparably of the unitive and procreative dimension, trascendence beyond the oneself, toward the other and toward the Other.